Is Faith a Form of Feeling? - Armstrong, A. C. (Harvard theological review, 1911)
Like the appeal to faith at large, the tendency to conceive faith as emotion may proceed from various motives. In contrast to an arid intellectualism, or with a view to curing practical corruption, it is urged in furtherance of earnest religious experience. This was the case in the pre-reformation and the Reformation age, and again during the revival in the eighteenth century in England. In eras of doubt the faith of feeling is commended as a substitute for the halting processes of reason, with their dubious or negative conclusions. This motive also was active in the era of renascence and reform, and it has markedly influenced the religious development of later modern times. Such motives, moreover, rest upon a basis of truth. The heart has its rights as well as the head, and its deliverances possess an evidential value. In periods of intellectual change the witness of the heart gains special importance as an aid to faith until the reason can adjust itself to the new conditions. The faith which purifies and the faith which inspires is always the faith which is experienced. These principles need emphasis now less than ever before, for there has never been a period in which they have been so often advocated, and with so great authority, as in the last century and a half. In our own time, in part by voices which have only lately ceased to speak to us, they have been urged with a persuasive eloquence that has carried them throughout the civilized world. Formulated in technical fashion, they have entered into the reflection of the age until they have become one of its most characteristic and most significant philosophies of religion.